IMPLEMENTASI METODE CONTENT-BASED FILTERING DENGAN PENDEKATAN EUCLIDEAN DISTANCE DALAM SISTEM REKOMENDASI PRODUK SKINCARE - Euis Halimatussa’diyah; Sekti Kartika Dini (LPPM Universitas Abdurrab, 2025)
The cosmetics industry in Indonesia is experiencing rapid growth, driven by increasing public awareness of self-care and the development of e-commerce. Skincare is one of the main segments with the largest market, but the many product choices often make it difficult for consumers to determine products that suit their preferences. In addition, the issue of overclaims on skincare which has been widely discussed since September 2024 has raised concerns among the public in choosing skincare products. In response to these conditions, this research was conducted with the aims to help users choose skincare products based on specified criteria, namely category, active ingredients, and expected benefits. The method used is Content-Based Filtering with the Euclidean Distance approach to calculate the similarity between products. The recommendation system was developed using Gradio as an interactive interface and hosted through the Hugging Face platform so that it can be accessed online. Based on three experiments conducted, an average precision value of 96.67% was obtained, which shows that the system is able to provide recommendations that are relevant to user preferences.